A revision of Gasteruption Latreille (Hymenoptera: Gasteruptiidae) in the Neotropical Region - Macedo, Antonio Carlos Cruz (Zootaxa, 2011)
The Neotropical species of Gasteruption Latreille are revised, described, diagnosed, and illustrated; a key for females is provided. Twenty six valid species are recognized, thirteen of which are described as new: G. amputatum Townes, G. barnstoni (Westwood), G. bertae n. sp., G. bispinosum Kieffer, G. brachychaetum Schrottky, G. brandaoi n. sp., G. brasiliense (Blanchard), G. floridanum (Bradley), G. glauciae n. sp., G. guildingi (Westwood), G. hansoni n. sp., G. helenae n. sp., G. huberi n. sp., G. kaweahense (Bradley), G. lianae n. sp., G. loiaconoae n. sp., G. masneri n. sp., G. oliveirai n. sp., G. parvum Schrottky, G. rafaeli n. sp., G. sartor Schletterer, G. smithi n. sp., G. tenue Kieffer, G. townesi (Alayo), G. visaliae (Bradley), and G. wahli n. sp. The following new synonymies are proposed: G. maculicorne Cameron, G. macroderum Schletterer, and G. zapotecum Schletterer with G. barnstoni; G. bihamatum Kieffer, G. fallens Kieffer, G. fiebrigi Schrottky, G. leptodomum Kieffer, G. montivagum Kieffer, and G. strandi Kieffer with G. bispinosum; G. annulitarse Schrottky, G. brasiliae Kieffer, G. gracillimum (Schletterer), G. longicauda Kieffer, G. petroselini Schrottky, G. subtropicale Schrottky and G. torridum (Bradley) with G. brasiliense; G. rufipectus (Westwood) with G. guildingi; G. angustatum (Kieffer) with G. kaweahense; G. horni Brèthes with G. parvum. The following taxa are considered as species inquirendae: G. albitarse Schletterer, G. austini Jennings and Smith, G. subcoriaceum Kieffer n. stat., and G. tenuicolle Schletterer. As well, G rubrum Taschenberg is synonymized with Pseudofoenus infumatus (Schletterer). In addition, G. tenue Pasteels, 1957a from Australia is a junior homonym of G. tenue Kieffer, 1922 and is renamed G. pasteelsi n. name.